Effective methods of protection of the intellectual activity results in infosphere of global telematics networks - D. A. Lovtsov (Открытое образование (Москва))
The purpose of this article is perfection of using metodology of technological and organization and legal protect of intellectual activity results and related intellectual rights in information sphere of Global Telematics Networks (such as of «Internet», «Relkom», «Sitek», «Sedab», «Remart», and others). On the conduct analysis base of the peculiarities and possibilities of using of different technological, organization and legal methods and ways protection of information objects the offers of perfection of corresponding organization and legal safeguarding are formulated. The effectiveness of the protection is provided on the basis of rational aggregation technological, organization and legal methods and ways possible in a particular situation.